2009
DOI: 10.1007/s00535-009-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot trial of body weight reduction for nonalcoholic fatty liver disease with a home-based lifestyle modification intervention delivered in collaboration with interdisciplinary medical staff

Abstract: The reduction in body weight achieved by NAFLD patients during the 6-month intervention was associated with improved fat deposition and liver function. This intervention offers a practical approach for treating a large number of NAFLD patients with lifestyle modification therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 20 publications
1
92
0
3
Order By: Relevance
“…In addition, the most important modification for an individual with ASH is the cessation of alcohol consumption and improved dietary habits. Considerable recent work has reviewed the previous studies, strategies, and recommendations of lifestyle modification as treatment for steatohepatitis (59,97,130,143,156), and new human trials continue to be reported describing successful treatment of liver pathology utilizing lifestyle modification paradigms (89,152,164). Managing body weight is likely the best overall method in the treatment of NASH.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…In addition, the most important modification for an individual with ASH is the cessation of alcohol consumption and improved dietary habits. Considerable recent work has reviewed the previous studies, strategies, and recommendations of lifestyle modification as treatment for steatohepatitis (59,97,130,143,156), and new human trials continue to be reported describing successful treatment of liver pathology utilizing lifestyle modification paradigms (89,152,164). Managing body weight is likely the best overall method in the treatment of NASH.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…Previous studies have reported a beneficial effect of a recommended diet combined with an increase in physical activity on the progression of NAFLD [6] . One study showed that a 7% to 10% weight reduction through intensive lifestyle intervention would lead to improvements in biochemical and histological features of nonalcoholic steatohepatitis (NASH) [7] .…”
Section: Introductionmentioning
confidence: 97%
“…At the end of six months, the interference of hepatic enzymes and the ratio of liver to spleen improved in these people. 90 Determining the therapeutic effect of weight loss in the clinical trial has two restrictions as follow: the first restriction is due to the little number of samples in the study and the second one is to determine the effect of weight loss on liver histology because liver biopsy is performed in the studies due to ethical considerations. The liver biopsy is essential for evaluating the effect of weight loss on hepatic steatosis.…”
Section: Weight Lossmentioning
confidence: 99%